Análise da distribuição espacial da Leishmaniose nos Municípios de Nova Esperança do Piriá, Paragominas e Ulianópolis-PA - LEITE, Fabiana Cardoso (2024)
This article describes research on the influence of environmental imbalances on American cutaneous leishmaniasis in the municipalities of Nova Esperança do Piriá, Paragominas, Ulianópolis, with their economies focused on different sectors, the main ones being agribusiness, in particular, soybean, eucalyptus, livestock agriculture and mining. The method is used through remote sensing observations, allowing the analysis of changes in land use and occupation and how fires in the regions, deforestation, agricultural expansion and mining influence the spread of the disease. Therefore, through research results, environmental degradation and biodiversity imbalance are factors for the proliferation of transmission vectors between disease reservoirs and parasites, causing the incidence of the disease in rural and urban regions.